Rancang Bangun Pintu Gerbang Secara Otomatis Berbasis IoT Menggunakan Aplikasi Blynk - Syaroni, Ahmad; Abrianto, Heru; Sidik, Ahmad Darmawan; Irmayani, Irmayani (Journal Scientific of Mandalika (JSM) e-ISSN 2745-5955 | p-ISSN 2809-0543, 2025)
Currently very rapid technological advances make it possible for various efforts to provide convenience and comfort for humans. One effort to provide convenience and comfort is through the development of home automation systems (Home Automation). One automation system that can be implemented at home is a system that can open the gate automatically without having to get out of the vehicle. Through the development of this system, it is hoped that house residents can open the gate from a certain distance without having to interact directly with the gate. Based on technological developments, especially in the field of electronics, telecommunications and applications, there is a microcontroller system, namely Arduino Uno, which can be used by humans to communicate with Android smartphones via the NodeMcu Esp8266, so that it can be used for gate opening applications without using conventional methods, but is quite accessible. via an Android smartphone only, the overall circuit of the gate system with Android control is divided into 3 parts, including: power supply, input section and output section. The power supply section is the voltage input obtained through the adapter. The input section consists of 1 input, namely Android, Arduino uno R3 and NodeMcu Esp8266. The output section consists of a servo motor and buzzer and LED light.